Faktor yang Mempengaruhi Masyarakat Berpindah Provider Brand Kartu Seluler - Warseno Warseno; Po Abas Sunarya; Ageng Setiani Rafika (IJAcc, 2024)
This research aims to analyze the influence of Product Attributes, Variety Seeking Behavior and Promotion simultaneously (together) on Brand Switching Behavior. This study also aims to analyze the influence of Product Attributes, Variety Seeking Behavior and Promotion partially (individually) on Brand Switching Behavior. The object of this research is IM3 Ooredoo Cellular Card and the subject of this research is Yogyakarta’s people who have used another brand of cellular card and switched brands to IM3 Ooredoo Cellular Card. The number of samples in this study were 140 respondents who had been determined by purposive sampling. The tool used is Multiple Linear Regression Analysis (SPSS). Based on multiple linear regression analysis, the results obtained that Product Attributes, Variety Seeking Behavior and Promotion together (simultaneously) have a positive and significant influence on brand switching behavior. Product Attributes, Variety Seeking Behavior and Promotions also have a positive and significant influence on Brand Switching Behavior.